Treating Mental Illness Among Diabetic Black Male Adolescents: A Review. (March 2018) - Banks, Andrae; Fields, Lashawnda; O'Dwyer, Curtis; Scott, Marquisha Lawrence; Joe, Sean
Objective: To examine randomized controlled trials (RCTs) for treatment evidence for Black male adolescents suffering from comorbid mental illness and diabetes mellitus. Method: A review of the studies published in English-language journals was conducted. Results: We found no RCT focused on Black males with diabetes mellitus Type 2 (DMT2). However, we found RCT inclusive of Black male adolescents with diabetes mellitus Type 1 (DMT1). Multisystemic therapy appears to be the best supported overall treatment for DMT1 management and psychosocial functioning followed by an enhanced form of behavioral family systems therapy for diabetics. Metformin was the only treatment in this review noted for use within DMT2. Metformin and a nursing-based telephone case management intervention realized utility as secondary services. Conclusions: There are gaps present for what effectively treats comorbid mental illness and DMT2 in Black male adolescents. For comorbid mental illness and DMT1, there are gaps in additional efficacious treatments, effectiveness across conditions, and effect duration beyond 24 months.